Training of Prevention from Bullying to Teachers in The Sangkhom Islam Wittaya School Thailand - Titin Indah Pratiwi; Budi Purwoko; Asieline Wahyu Triardyanti; Puput Randika Agustin; Qurrota A’yuni Nur Rohmah; Frisya Putri Aulia (Al-Qalam Institute, 2025)
Bullying at schools can happen in the form of physical violence, intimidation, mockery, social excommunication, and other violence actions. Bullying can cause psychological disturbance such as depression, anxiety, stress, unsecure, and unconfident. Teachers must have skills to prevent students from bullying. The training was conducted to teachers such that they can avoid bullying happens at their school. The training was conducted by online and offline method. In the offline method some a simulation was conducted. The improvement of soft skills of teachers in preventing bullying to happen was detected.